Overview Of Psychotic Disorder In Adolescents - Jihan Azzubaidi; Nur Isra; R. Joko Maharto (Sean Institute, 2024)
The adolescent phase is a transition phase from childhood to adulthood. A number of studies suggest that psychotic experiences are more common in children and young adolescents compared with adults but few longitudinal studies have assessed psychotic phenomena at multiple points in time using semi-structured interviews, and none have assessed such experiences sequentially from childhood until adolescence. In one study the incidence rate of psychotic experiences increased between ages 13 and 24, peaking in late adolescence . Method Which used that is literature review. The results obtained in this literature were that there were 8 articles obtained with a year limit 2019 – 2024 and that's it done analysis about description psychotic on teenager. Conclusion: teenagers are vulnerable to mental health problems, including psychotic disorders such as schizophrenia. Maintenance Which appropriate And support family important For recovery teenager Which experience psychotic. .